The effectiveness of a meaning-based approach in teaching subject-verb agreement to Indonesian EFL college students - Rianto, Agus (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1999)
Indonesian college students, who are pursuing their studies in institutions of higher learning where English is used as the main medium of instruction, need to demonstrate a high proficiency of the English language in order to succed academically. Here, they are not only expected to comprehend academic texts in English but to produce acceptable texts of their own as well. However, many such students are unable to do so because their previous training has not prepared them to organize textual information in a manner expectged by a native speaker of English. They are unable to write clearly and coherently--a problem related to their lack of control of the grammatical system of English. In this experimental study, the effectiveness of a meaning-based approach to grammar teaching is examined in the context of Indonesian EFL college students. The present study, conducted at the Institut Agama Islam Negri (IAIN)--State Institute for Islamic Studies, Medan, North Sumatra, Indonesia, investigated the grammatical competency of 46 undergraduate students from the faculty of Tabriyah (Education). This study explores the questions of whether or not there are significant differences in the occurrence of zero (0) and -s morphemes attached to nouns and verbs in the subjects' essays written before and after instruction and between the higher proficiency students and the lower proficiency students. A time-series design was used in which the 46 subjects were administered a series of pretests, a two week meaning-based treatment, and a series of posttests. Results indicate that the students received immediate benefits from the meaning-based instruction. There were some improvements in the students' posttest essays in terms of reducing incoherent message andincreasing coherent messages associated with the use of the zero (0) and -s morphemes with verbs and nouns. The findings of this study also showed that there is variability in the performance of the subjects in acquiring those grammatical features. This raises an important question for further research: whether or not such variance in performance can be checked with a long-term exposure to grammatical systems via the meaning-based approach. The researcher believes that cyclical procedures would help reduce such variance in performance.